A wide linear range and stable H2O2 electrochemical sensor based on Ag decorated hierarchical Sn3O4. (20th March 2017) - Tian, Liangliang; Xia, Kaidong; Hu, Wanping; Zhong, Xiaohui; Chen, Yanling; Yang, Cong; He, Gege; Su, Yongyao; Li, Lu
Abstract: Due to high electrocatalytic activity, Ag nanoparticles (Ag NPs) always be a good candidate for electrochemical sensors. However, it suffers from the aggregation problem during synthesis, storage and immobilization process. In this paper, hierarchical Sn3 O4 was selected as scaffold for Ag NPs to prevent aggregation and ensure the stability. As a sensitive electrode to detect H2 O2, Ag/Sn3 O4 exhibits wide linear range and reliable stability, which can be attributed to the hierarchical structure, strong immobilization of Ag NPs and structural, physical and chemical stability of Sn3 O4 scaffold. It was concluded that the hierarchical Ag/Sn3 O4 architecture has potential applications in the design of nonenzymatic H2 O2 sensors and the load of Ag NPs on heterovalent tin oxides demonstrates a promising way for building H2 O2 detection electrodes.